2006
DOI: 10.1007/s11199-006-9042-y
|View full text |Cite
|
Sign up to set email alerts
|

Body Objectification, Self-Esteem, and Relationship Satisfaction: A Comparison of Exotic Dancers and College Women

Abstract: We examined body objectification, self-esteem, and relationship satisfaction differences between college women and exotic dancers and the relationships among these measures for both groups. Forty-three college women and 40 female exotic dancers completed a questionnaire that assessed each of these constructs. Relative to college women, exotic dancers reported less relationship satisfaction, more body surveillance, and a greater prioritizing of body attractiveness over physical competence. Relationship satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
2
23
2
1
Order By: Relevance
“…The obtained positive finding for belly dance is similar to those found previously for street dance (Swami and Tovée 2009) and modern dance (Langdon and Petracca 2010). It is in marked contrast to the one previous finding for exotic dance (Downs et al 2006), whereby United States exotic dancers had poorer body image than college students. Thus the categorization of belly dance as akin to exotic dance in this way (Langdon and Petracca 2010) does not hold.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The obtained positive finding for belly dance is similar to those found previously for street dance (Swami and Tovée 2009) and modern dance (Langdon and Petracca 2010). It is in marked contrast to the one previous finding for exotic dance (Downs et al 2006), whereby United States exotic dancers had poorer body image than college students. Thus the categorization of belly dance as akin to exotic dance in this way (Langdon and Petracca 2010) does not hold.…”
Section: Discussionsupporting
confidence: 85%
“…As yet there exists little quantitative research on the body image of Australian or other belly dancers, but in their preliminary survey of U.S. belly dancers, Downey et al (2010) reported that the vast majority saw belly dance as a positive influence on their feelings about their body (and none cited it as a negative influence). Consequently, in contrast to Downs et al (2006) finding for U.S. exotic dancers, we predicted that belly-dancers would show less body dissatisfaction and more positive body image than non-belly dancing college students.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…U.S. college women who devalue their overall self-worth also tend to hold their bodies in low esteem. Low self-esteem predicts body dissatisfaction among college women (Tylka and Subich 2004) and low self-esteem is associated with body shame among exotic dancers (Downs et al 2006 Body comparison is also likely to predict body shame in the model (see path i). Canadian, Australian, and U.S. women who compared their bodies or body parts to others perceived as more attractive (i.e., upward social comparison), such as those who resemble the thin-ideal, experienced body image distress (Morrison et al 2004;Paxton et al 1999;Thompson et al 1999;van den Berg et al 2007).…”
Section: Our Proposed Integrative Modelmentioning
confidence: 99%
“…Being judged as bad, sex workers often get disrespectfully treated, both by intimates (Bradley, 2007) and by the society at large (Bruckert, & Chabot, 2010;Pryen, 1999). Some sex workers manage to maintain a good self-esteem in spite of this (Bernstein, 2007;Downs, James, & Cowan, 2006;Griffith, Mitchell, Hart, Adams, & Gu, 2012). However, many internalize this social perception that they are being bad and despicable, suffer a consequent loss of self-esteem and have to struggle to still maintain some good self-esteem (Benoit & Millar, 2001;Clouet, 2008;Orchard, Farr, Macphail, Wender & Young, 2012;Pryen, 1999;Sanders, 2004b).…”
Section: Introductionmentioning
confidence: 99%